Introduction to dossier Community strategies for confronting socio-environmental conflicts: Beyond resistance - van Teijligen, Karolien; Dupuits, Emilie (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2021)
Introduction to dossier "Community strategies for confronting socio-environmental conflicts: beyond resistance"